2008
DOI: 10.1175/2007jamc1480.1
|View full text |Cite
|
Sign up to set email alerts
|

Climate, Extreme Heat, and Electricity Demand in California

Abstract: Climate projections from three atmosphere-ocean climate models with a range of low to mid-high temperature sensitivity forced by the Intergovernmental Panel for Climate Change SRES higher, middle, and lower emission scenarios indicate that, over the 21 st century, extreme heat events for major cities in heavily air-conditioned California will increase rapidly. These increases in temperature extremes are projected to exceed the rate of increase in mean temperature, along with increased variance. Extreme heat is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
110
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(111 citation statements)
references
References 19 publications
1
110
0
Order By: Relevance
“…We selected the state of California as a model system owing to its relatively early, rapid, and ambitious deployment of solar energy systems, 400,000 km 2 of land area (greater than Germany and 188 other countries), large human population and energy demands, diverse ecosystems comprising 90% of the California Floristic Province biodiversity hot spot, and its long-standing use in elucidating the interrelationship between land and energy (9,10,22,23).…”
Section: Significancementioning
confidence: 99%
“…We selected the state of California as a model system owing to its relatively early, rapid, and ambitious deployment of solar energy systems, 400,000 km 2 of land area (greater than Germany and 188 other countries), large human population and energy demands, diverse ecosystems comprising 90% of the California Floristic Province biodiversity hot spot, and its long-standing use in elucidating the interrelationship between land and energy (9,10,22,23).…”
Section: Significancementioning
confidence: 99%
“…There would likely be competing effects with a negative impact from increasing extreme hot temperatures and a positive impact from decreasing extreme cold temperatures (Mills et al 2013b). Similarly, changes in extreme temperature would affect energy demand, with increasing extreme hot events leading to higher usage of air conditioning (Miller et al 2008;McFarland et al 2013). However, decreasing extreme cold temperatures would reduce the use of fuels for heating (Mansur et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, extreme warm temperatures in the California region have mostly occurred in July and August (Gershunov and Cayan 2008), but as climate warming takes hold, the occurrences of these events will increase in frequency and magnitude (Hayhoe et al 2004;Gershunov and Douville 2008;Miller et al 2008) and likely will begin in June and could continue to be found in September. All simulations indicate that hot daytime and nighttime temperatures (heat waves) increase in frequency, magnitude, and duration from the historical period and during the projected period through the first half of the twenty-first century (Table 1).…”
Section: Heat Wavesmentioning
confidence: 99%